Analysis of Factors that Shape the Use of Information Technology in Aron Group Companies - Retika, Steward; Herdinata, Christian (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
This study aims to determine the factors that shape the use of information technology in Aron Group companies. In this study, there are 24 variables that are used as factors that are assumed to shape the use of information technology, so that the results can be used by Aron Group to develop a strategy framework in order to implement and provide better and targeted use of information technology. Researchers use quantitative types of research. In this study, there were as many as 86 people used as samples. The analysis method used in this study is exploratory factor analysis (EFA) with the help of the SPSS application. The results of this study are the main factors forming the use of information technology are work competence factors and their elements, organizational environmental factors and their elements, task suitability factors and their elements, work motivation factors and their elements.